PENGARUH PUPUK BIO-SELURRY YANG DIPROSES DENGAN EM4 DAN MA-11 TERHADAP PERTUMBUHAN RUMPUT ODOT (Pennisetum purpureum CV. Mott) DALAM SISTEM TUMPANG SARI DENGAN LEGUM Indigofera zollingeriana: THE EFFECT OF BIO-CELLURRY FERTILIZER PROCESSED WITH EM4 AND MA-11 ON THE GROWTH OF ODOT GRASS (PENNISETUM PURPUREUM CV.MOTT) IN AN MIXED CROPPING SYSTEM WITH THE LEGUM INDIGOFERA ZOLLINGERIANA - Romadhoni, Iskhak; Purwadi, Purwadi; Prasetyo, Aris Budi (Tropical Animal Science, 2025)
This study aims to determine the effect of organic fertilizer bio-selurry processed using Effective Microorganisms 4 (EM4) and MA-11 on the growth of odot grass (Pennisetum purpureum cv. Mott) intercropped with legume Indigofera zollingeriana. The study was conducted from January to March 2025 in Ampel District, Boyolali Regency. The experimental design used was a Completely Randomized Design (CRD) with 4 treatments and 5 replications, namely P0 (bio-selurry without addition), P1 (bio-selurry + EM4), P2 (bio-selurry + MA-11), and P3 (bio-selurry + EM4 + MA-11). The parameters observed included the time of first shoot emergence, number of shoots, number of leaves, leaf blade length, stem diameter, fresh forage production, and dry matter. The results showed that the treatment of bio-selurry fertilizer had no significant effect (P>0.05) on the first shoot, number of shoots, number of leaves, leaf length, stem diameter, and dry matter. However, there was a significant effect (P<0.05) on the production of fresh greens, with the highest results obtained in treatments P2 and P3. This indicates that the use of bio-selurry fertilizer fermented with EM4 and MA-11 can increase the production of odot grass greens, although it has not significantly affected other growth parameters in the early phase.